Analysis of Financial Technology Implementation on The Quality Of Banking Services in Indonesia: SWOT Analysis - Dr SB Goyal; Eka Purnama Harahap; Nesti Annggraini Santoso (Pandawan Sejahtera Indonesia, 2022)
It is widely expected that Indonesian banks will significantly improve their services to reach a broader range of customers, especially those in the 3T region. However, only a tiny percentage of the contacts to companies in the 3T region is made by Indonesian banks. In the face of this issue, he prepares and conducts his SWOT analysis of FinTech policies to improve Indonesian banking services, especially by extending their offerings to a more significant segment of Indonesian society. Stakeholders in the banking industry can better understand the importance of good bank governance based on fear of God and respect for others when managing internal and external assets encompassing all banking aspects. This study explores relevant banking literature to learn more about the SWOT (Strengths, Weaknesses, Opportunities and Threats) of implemented financial techniques on the quality of banking services in Indonesia in the digital age